NILAI-NILAI NASIONALISME PADA PUISI DONGENG PAHLAWAN KARYA WS. RENDRA - Sunarti Sunarti; Maulana Yusup; Heri Isnaini (IKIP Siliwangi, 2022)
This article discusses the values of nationalism in W.S. Rendra's poem